120k views
5 votes
Simplify the expression below 13y+x-7y

User CesarGon
by
6.4k points

2 Answers

2 votes

Answer:

=x+6y

Let's simplify step-by-step.

13y+x−7y

=13y+x+−7y

Combine Like Terms:

=13y+x+−7y

=(x)+(13y+−7y)

=x+6y

Answer:

=x+6y

User Ruslan Plastun
by
6.2k points
4 votes

Answer: 5y + x

Step-by-step explanation: As you first step to this problem, change all your minus signs to plus negatives.

To simplify, we can only combine what are called our like terms and in this problem, we have one y-term and we have a pair of like terms in our x-terms.

So let's start by combining our y-terms.

13y + -7y simplifies to 5y.

Now we have one x-term so we have 5y + x.

User Ray Hulha
by
6.2k points